Implementasi Pelayanan Malam Di Wilayah Kecamatan Bulak Kota Surabaya - Adein Benu; Mahardani Febrihapsari; Muthowif Muthowif; Suripno Suripno (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to determine and analyze the implementation of the Night Service in Bulak District. The research method uses a qualitative descriptive approach which produces data in the form of written words from interviews, observations and documentation. The focus of this study uses the suitability model of program implementation by David C. Korten. The results of this study indicate that the night service program has received a positive response by being the answer to public complaints so that public services provided by the government can be closer, easier, and less complicated. This is supported by the ability of officers in night services as a whole, the community of Bulak District responded positively. Because it is in accordance with what is expected by the community, namely providing services in a friendly, polite, fast, thorough, and informative manner, although there are still visible officers who look tired. Interestingly, the community is also involved in evaluating the performance of the implementers, namely the night service officers in order to improve service quality standards.